A review of surrogate motherhood regulation in south American countries: pointing to a need for an international legal framework - Gloria Torres; Anne Shapiro; Tim K. Mackey (BMC, 2019)
Abstract Background Advances in science and technology coupled with globalization are changing access to and utilization of reproductive health services. This includes the transnational phenomenon of families who use surrogate mothers to reproduce, with forms of altruistic and commercial surrogacy becoming more commonplace. Simultaneously, changes in law, regulation, and policy are necessary to protect surrogates, intended parents, and resulting children. These developments have been slow to adapt to challenges inherent to surrogacy arrangements, most specifically in low-and middle-income countries, including in South American countries. Methods We conducted an interdisciplinary non-systematic literature review and legal analysis of existing and pending policy, laws, and regulations related to commercial surrogacy arrangements in Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru, Uruguay, and Venezuela. The review focused on articles that discussed topics of domestic and international law, policy, regulation, and governance related to commercial surrogacy. We queried PubMed, JSTOR, and Google Scholar for Spanish and English-language articles limited to those published between 2000 and 2016. Results Our literature and legal review found a wide variance in how different countries address the issue, including two (Brazil and Uruguay) that have issued guidance attempting to clarify the legality of commercial surrogacy, others who have introduced surrogacy-specific legislation, and a final group with no specific legal mechanisms in place. Our extracted legal case studies also indicate that courts have a hard time interpreting existing law and its applicability to surrogacy. The influence of Catholicism also played a role in the adoption of surrogacy and other advanced reproductive technology (ART)-related legislation. Conclusions Changes in global infertility rates, the emergence of new family structures, and advancement of ART are factors that will influence future development of legal frameworks addressing surrogacy in South America. Despite a growing transnational market for commercial surrogacy in many of the countries examined, the current patchwork of policy does little to clarify what forms of surrogacy are legally permissible, nor do they adequately protect surrogates, intended parents, or the children themselves. This points to an urgent need for regional legal and policy harmonization specifically designed to align with public health and human rights principles.